2020
DOI: 10.1038/s41467-020-15186-z
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment tumor-related leukocytosis misleads positron emission tomography-computed tomography during lymph node staging in gynecological malignancies

Abstract: The accuracy of fluorine-18-fluorodeoxyglucose positron emission tomography-computed tomography (18F-FDG-PET/CT) can be influenced by the increased glycolytic activity of inflammatory lesions. Here, using clinical data obtained from gynecological cancer patients, tumor samples and animal models, we investigate the impact of pretreatment tumor-related leukocytosis (TRL) on the diagnostic performance of 18F-FDG-PET/CT in detecting pelvic and paraaortic lymph node metastasis. We demonstrate that pretreatment TRL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 33 publications
4
37
0
1
Order By: Relevance
“…These studies support a model where myeloid cells including TAM consume the most glucose in the TME. Consistent with our findings, myeloid infiltration is known to drive FDG avidity in nontumor bearing lymph nodes in human and mouse gynecological malignancies 24 . Our data extend these findings directly to the solid TME.…”
Section: Tme Myeloid Cells Uptake More Glucose Than Other Cell Types supporting
confidence: 92%
“…These studies support a model where myeloid cells including TAM consume the most glucose in the TME. Consistent with our findings, myeloid infiltration is known to drive FDG avidity in nontumor bearing lymph nodes in human and mouse gynecological malignancies 24 . Our data extend these findings directly to the solid TME.…”
Section: Tme Myeloid Cells Uptake More Glucose Than Other Cell Types supporting
confidence: 92%
“…Immunocompetent C57BL/6 mice were subcutaneously inoculated with 1.0 × 10 6 ID-8 cells/mouse. Fourteen days after inoculation, mice were randomized into 2 groups that were administered either Gr-1 antibody (n = 5) or PBS (n = 5), every other day (day 14,16,18,20). Kaplan-Meier estimates of survival is shown.…”
Section: Discussionmentioning
confidence: 99%
“…Sixty minutes after injection, PET measurements were performed in an abdominal position using a small-animal FDG-PET/CT scanner (Inveon MM; Siemens Medical Solutions, Knoxville, USA). The image data acquired from the small-animal FGD-PET/CT scanner were displayed and analyzed with RadiAnt DICOM 4.6.9 Viewer (Medixant, Poznan—Poland), as reported previously 16 .…”
Section: Methodsmentioning
confidence: 99%
“…These processes are regulated by MDSC-derived mediators, including vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), Bv8, and matrix metalloproteinase (MMP)-9, all of which are essential for tumor angiogenesis and cancer cell invasion [11,14]. Moreover, recent reports suggested that MDSCs stimulate the metastatic activity of cancer cells by facilitating epithelial-to-mesenchymal transition (EMT) or by creating "premetastatic niches" [15,16]. Importantly, the evidence has indicated that MDSCs induce "stemness," which might be associated with resistance to existing anticancer treatments including chemotherapy or radiotherapy [17].…”
Section: Nonimmune Activities Of Mdscmentioning
confidence: 99%